Integrated ordered structure material as well as preparation method and application thereof

By using a combination design of a high enthalpy bottom layer and a low infrared emissivity top layer in infrared stealth materials, the phase change enthalpy absorption heat and multi-stage reflection of metal fillers achieve "hot camouflage" of apparent temperature, solving the problem of poor infrared camouflage effect in existing materials in high temperature environments, and achieving compatibility stealth protection for static and dynamic heat sources.

CN119758490AActive Publication Date: 2025-04-04ZHEJIANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411710475.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-04
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing infrared stealth materials are difficult to achieve long-term effective infrared camouflage in high temperature environments, and their compatibility with static and dynamic heat sources is insufficient.

Method used

The integrated ordered structural materials are adopted, including a high enthalpy bottom layer and a low infrared emissivity top layer. The high enthalpy bottom layer absorbs heat through phase change enthalpy, and the low infrared emissivity top layer achieves "hot camouflage" of apparent temperature through multi-stage reflection of metal fillers.

Benefits of technology

It realizes reliable infrared stealth in a wide temperature domain, with heat absorption, heat insulation and low radiation properties, and can show excellent compatibility and stealth protection capabilities for both static and dynamic heat sources, breaking the dependence of traditional materials on narrow application temperature zones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119758490A_ABST
    Figure CN119758490A_ABST
Patent Text Reader

Abstract

The invention discloses an integrated ordered structure material as well as a preparation method and application thereof. The prepared integrated ordered structure material comprises a high-enthalpy bottom layer and a low-infrared-emissivity top layer which are arranged in sequence, the high-enthalpy bottom layer is a thermally stable gel layer immobilized by a high-capacity phase change material, and the low-infrared-emissivity top layer is an infrared transparent resin layer filled with metal filler. The infrared thermal stealth material prepared by the preparation method disclosed by the invention not only can cope with reliable infrared stealth in a wide temperature range, but also can show excellent compatible stealth protection capability on static and dynamic heat sources, shows reliable infrared'false 'capability, successfully breaks through the dependence of a traditional material on a narrow application temperature range, and has a wide application prospect in the field of long-term infrared thermal stealth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of stealth materials, in particular to the technical field of infrared stealth materials. Background Art

[0002] Unlike visible light and radar detection, which use reflected signals to obtain information, infrared radiation is passive and therefore needs to be hidden. According to the Stefan-Boltzmann law, the total amount of radiation emitted by an object is proportional to its emissivity and the fourth power of its absolute temperature. Therefore, the key to reducing radiation intensity and improving infrared stealth capabilities lies in reducing infrared emissivity and controlling the target surface temperature in order to improve the target's stealth effect.

[0003] Emissivity engineering is considered a promising approach, including but not limited to photonic crystals, doped semiconductors, and infrared coatings; among them, the unique filtering properties of photonic crystals can effectively reduce the emissivity of the atmospheric window, as shown by Zhang et al. (J.-K. Zhang, J.-M. Shi, D.-P. Zhao, Y.-Z. Chen, Optical Engineering. 2017,56.) A one-dimensional heterostructure photonic crystal was obtained by vacuum evaporation sputtering of Te and ZnSe, and the emissivity of the one-dimensional heterostructure photonic crystal in the 3-5-μm and 8-14 μm bands was 0.072 and 0.194, respectively; the adjustability and compatibility of semiconductor doped infrared stealth technology are attractive in multi-band stealth, such as Xu et al. (C. Xu, B. Wang, M.Yan, Y. Pang, Y. Meng, W. Wang, J. Wang, Q. Fan, S. Qu, Infrared Physics & Technology. 2020, 105.) designed a metasurface with an ITO / dielectric / ITO sandwich structure and obtained a low infrared emissivity of 0.52 by adjusting the filling rate of ITO. Infrared coatings can hide objects from infrared detection due to their high infrared reflectivity, which has become a new area of ​​interest, such as Huang et al. (X. Huang, W. Rao, Y.Chen, W. Ding, H. Zhu, M. Yu, J. Chen, Q. Zhang, Journal of Materials Science: Materials in Electronics.2016, 27, 5543-5548.) Cheap and readily available homogeneous aluminum was used as a metal filler to integrate into different resin substrates, and the effects of different simple coating methods such as spraying, brushing, scraping and flow on the radiation characteristics of the coating were compared. Finally, an infrared coating with an emissivity of 0.31 was obtained by spraying. From the perspective of scalability, the preparation method of the infrared coating is simple and can be quickly implemented without changing the target shape and structure. It is not limited by the target geometry and structure, which is conducive to large-scale and comprehensive application.

[0004] In order to meet the long-term camouflage requirements in a wide temperature range, we need to improve the versatility of stealth methods, and combining thermal management technology with emissivity engineering is a potential and reliable way to solve this problem; Chen et al. (X. Chen, S. Guo, S. Tan, J. Ma, T. Xu, Y. Wu, G. Ji, Carbon. 2023, 213.) Chitosan-derived carbon aerogel is used as the skeleton, and vanadium dioxide (VO2), a transition metal phase change material with thermotropic emissivity, is loaded; the emissivity of the resulting composite structure can gradually decrease with increasing temperature, and reaches 0.581 at 100°C; the average temperature of the composite structure after standing for 180s in a 120°C environment is 32.8°C, showing excellent thermal stealth performance; however, this type of biomass-derived carbon aerogel is often very strong; although this allows it to withstand loads of 3000 to 5000 times its own weight, it also makes it lose its elasticity and flexibility (it cannot fit any target).

[0005] Hydrogels have attracted widespread attention in many fields as ideal flexible substrates due to their flexibility, stretchability and biocompatibility; Zhu et al. (T.-y. Zhu, W.-j. Jiang, S. Wu, Z.-j. Huang, Y.-l. Liu, X.-d. Qi, Y. Wang, ACS Applied Materials & Interfaces. 2024, 16, 15372-15382.) Polyacrylamide was used to encapsulate sodium sulfate decahydrate and conductive filler MXene / PEDOT:PSS, and the surface temperature of the obtained flexible phase-change organic hydrogel was 42.1°C after covering a 65°C hot target for 6 minutes; In addition, Zhou et al. (Y.-C.Zhou, J. Yang, L. Bai, R.-Y. Bao, M.-B. Yang, W. Yang, Chemical Engineering Journal.2022, 446.) A flexible phase-change hydrogel with excellent mechanical and thermophysical properties was prepared by integrating a polyvinyl alcohol hydrogel substrate with paraffin phase-change microspheres (which can provide stealth protection against a 50°C heat source for nearly 30 minutes). Although the phase-change hydrogel exhibits excellent flexibility and stretchability, the large amount of water contained in it will evaporate and dissipate in the high temperature range, resulting in the infrared stealth based on hydrogel being mostly limited to the medium and low temperature range (i.e., below 70°C). In addition, since there is a threshold for the phase change heat absorption of phase change materials, it can only achieve short-term infrared stealth. At present, long-term infrared camouflage of important targets in extreme environments is still a huge challenge that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to solve the problems in the prior art and to propose an integrated ordered structure material and a preparation method and application thereof. The prepared integrated ordered structure material can not only cope with reliable infrared stealth in a wide temperature range, but also exhibit excellent compatible stealth protection capabilities for both static and dynamic heat sources, and demonstrate reliable infrared "false indication" capabilities, successfully breaking the traditional material's dependence on a narrow application temperature zone, and has broad application prospects in the field of long-term infrared thermal stealth.

[0007] To achieve the above object, the present invention is implemented through the following technical solutions: The integrated ordered structural material comprises a high enthalpy bottom layer and a low infrared emissivity top layer arranged in sequence, wherein the high enthalpy bottom layer is a thermally stable gel layer solidified by a high-capacity phase change material, and the low infrared emissivity top layer is an infrared transparent resin layer filled with metal fillers; wherein the high enthalpy bottom layer can utilize the phase change enthalpy to fully absorb the heat of the heat conduction process to increase the axial heat transfer resistance, while the low infrared emissivity top layer can utilize the metal fillers to reflect thermal radiation in multiple stages to achieve "thermal camouflage" of the apparent temperature.

[0008] Preferably, a high thermal resistance middle layer is provided between the high enthalpy bottom layer and the low infrared emissivity top layer, and the high thermal resistance middle layer is a polydimethylsiloxane resin layer. Among them, the high thermal resistance middle layer can effectively reduce the heat transfer in the structure, reduce the infrared radiation intensity of the local high temperature area, and make the surface temperature distribution of the structure more uniform to reduce the detectability of the target under the infrared detection equipment. On the other hand, it can also reduce the thermal stress effect of the temperature gradient on the infrared coating, thereby slowing down the aging and corrosion rate of the coating and extending the service life of the stealth system; this three-layer design allows the stealth system to have both heat absorption, heat insulation and low radiation performance, thereby organically combining thermal management technology with emissivity engineering.

[0009] Furthermore, the high thermal resistance middle layer is coated on all or part of the surface of the high enthalpy bottom layer except the bottom surface, and the low infrared emissivity top layer is coated on the top surface of the high thermal resistance middle layer; wherein, the high thermal resistance middle layer can enhance the adhesion between the high enthalpy bottom layer and the low infrared emissivity top layer to avoid desorption of the double layer due to stress friction; this is because the infrared transparent resin layer can utilize polar groups to form a strong chemical bond with the polydimethylsiloxane resin layer, so that the low infrared emissivity top layer exhibits excellent level 1 bonding strength.

[0010] Furthermore, the thickness of the high thermal resistance middle layer is controlled within the range of 3.0 to 5.0 mm, and the thickness of the low infrared emissivity top layer is controlled within the range of 220 to 280 um.

[0011] Furthermore, the high enthalpy bottom layer exhibits a progressively densely packed worm-like rod structure, and the low infrared emissivity top layer is in the form of metal fillers stacked in layers in the infrared transparent resin layer; wherein the low infrared emissivity top layer can reflect thermal radiation in multiple levels through the stacked layers of metal fillers, thereby reducing the stealth coating's absorptivity and emissivity of thermal radiation (Kirchhoff's law) and regulating the radiation temperature.

[0012] The method for preparing an integrated ordered structure material comprises the following steps: a) Preparation of the high enthalpy bottom layer: firstly, polyvinyl alcohol, fatty acid, acid reagent and aldehyde cross-linking agent are sequentially mixed and reacted, then the mixed solution is solidified and formed, and then washed and dried in sequence to obtain a fatty acid-based phase change gel layer as the high enthalpy bottom layer; b) Preparation of high thermal resistance middle layer: firstly, dimethylsiloxane monomer and cross-linking agent are uniformly mixed and poured into a mold with high enthalpy bottom layer, and then the mixed liquid is cured outside the high enthalpy bottom layer to form a high thermal resistance middle layer; c) Preparation of the low infrared emissivity top layer: First, the metal filler is evenly dispersed in the infrared transparent resin substrate, and then the dispersion is sprayed on the outside of the high thermal resistance middle layer and cured to form a low infrared emissivity top layer.

[0013] Preferably, in step a), the loading amount of the fatty acid is 60-80wt%, the mass volume ratio of the fatty acid to the acidic reagent is 0.001-0.003 g / ul, the volume ratio of the acidic reagent to the aldehyde cross-linking agent is 6-10:1, the fatty acid is one or a combination of capric acid, lauric acid, myristic acid, palmitic acid and stearic acid, the acidic reagent is hydrochloric acid, and the aldehyde cross-linking agent is one or a combination of formaldehyde, acetaldehyde, n-butyraldehyde, glutaraldehyde and crotonaldehyde; wherein the fatty acid is an alkanoic acid having general carboxylic acid chemical properties, and the aldehyde cross-linking agent is an aldehyde substance that can undergo a condensation reaction with polyvinyl alcohol under acidic conditions; in addition, stearic acid has a relatively high melting point (76°C) and thermal enthalpy (208.3 kJ / kg), has better heat absorption and heat storage capacity, and is naturally and widely available (can be extracted from vegetable oils and animal fats), so it is the preferred choice; Glutaraldehyde is the preferred choice because it has a dialdehyde structure and can more effectively chemically cross-link with polyvinyl alcohol through a condensation reaction to form a stable covalent bond, thereby significantly improving the material's degree of cross-linking and mechanical properties, heat resistance, chemical resistance, and biological and tissue compatibility.

[0014] Furthermore, in the step a), polyvinyl alcohol is first dissolved in deionized water and fatty acids and hydrochloric acid are added in sequence, and then an aldehyde cross-linking agent is added after stirring for a period of time and quickly transferred to a mold. After the phase change gel is formed (the phase change gel can be quickly formed within 5 minutes), it is demolded and washed with sufficient deionized water and dried in a vacuum oven to obtain a fatty acid-based phase change gel layer.

[0015] Furthermore, in the step a), polyvinyl alcohol is first dissolved at a temperature of 60 to 100° C., and then fatty acid, hydrochloric acid and aldehyde cross-linking agent are dissolved in sequence after the solution temperature drops to room temperature. The vacuum drying temperature is 45 to 65° C. and the vacuum drying time is 15 to 25 hours.

[0016] Preferably, in step b), the cross-linking agent is one or a combination of methyltrichlorosilane, trisilane and phenyltrichlorosilane, and the mass ratio of the dimethylsiloxane monomer to the cross-linking agent is 8 to 12:1.

[0017] Furthermore, in the step b), the mixed liquid is defoamed and then solidified outside the high enthalpy bottom layer.

[0018] Furthermore, in the step b), the defoaming is allowed to stand at room temperature for 20 to 40 minutes, the curing temperature is 45 to 65° C., and the curing time is 4 to 8 hours.

[0019] Preferably, in step c), the loading amount of the metal filler is 30-70wt%, the metal filler is one or a combination of aluminum powder, iron powder, zinc powder, silver powder and gold powder, the shape of the metal filler is one or a combination of spherical, rod-shaped, scaly and irregular, the maximum spacing between two points of the metal filler on the surface is controlled to be 20-25um, and the infrared transparent resin is one or a combination of fluorocarbon resin, epoxy resin, polyurethane resin and acrylic resin; wherein the infrared transparent resin is an infrared transparent material without strong absorption in the far infrared band; in addition, fluorocarbon resin has excellent heat resistance and chemical resistance due to its strong CF bond as the skeleton, can remain stable at high temperature and various chemical environments, and is particularly suitable for fields requiring long-term durability; metal fillers usually have a lower absorptivity due to the densely arranged atoms in a densely packed structure, thereby showing a lower emissivity in the infrared band; in terms of shape, scaly powder is preferred because it has a large diameter-to-thickness ratio and good spreadability, and is easy to float to the coating surface.

[0020] Furthermore, in the step c), the viscosity of the dispersion is adjusted by a viscosity regulator before being sprayed and is dried after being sprayed.

[0021] Furthermore, in the step c), the viscosity regulator is butyl acetate and the dispersion is adjusted to have good fluidity and no obvious particles formed by filler agglomeration are observed, and the dispersion is allowed to stand and defoam for 10 to 14 hours at room temperature, the curing temperature is 45 to 65° C., and the curing time is 4 to 8 hours.

[0022] The application of integrated ordered structure materials in infrared stealth; taking the three-layer structure as an example, on the one hand, the thermally stable gel layer (i.e., the high-enthalpy bottom layer) with high-enthalpy characteristics and high-capacity phase change material immobilized will serve as a super heat absorption layer and form a thermal barrier together with the polydimethylsiloxane resin layer (i.e., the high thermal resistance middle layer) with high thermal resistance characteristics to achieve dynamic coordinated temperature control; on the other hand, the low infrared emissivity top layer can utilize the multi-level reflection of infrared waves by metal fillers to show low infrared emissivity; this design that combines thermal management technology with emissivity engineering can easily achieve long-term concealment effect for infrared detection; the integrated ordered structure material has the functions of heat absorption, heat insulation and thermal radiation attenuation, and can achieve reliable and persistent infrared stealth for both static and dynamic high-temperature heat sources.

[0023] Beneficial effects of the present invention: 1) By using a high enthalpy bottom layer and a low infrared emissivity top layer together as the base layer, on the one hand, the high enthalpy bottom layer can fully absorb the heat of the heat conduction process by utilizing the phase change enthalpy to increase the axial heat transfer resistance, and on the other hand, the low infrared emissivity top layer can utilize the metal filler to reflect the thermal radiation in multiple stages to achieve the "thermal camouflage" of the apparent temperature; 2) By adding a high thermal resistance middle layer between the high enthalpy bottom layer and the low infrared emissivity top layer to form a sandwich-like composite system, it not only combines efficient heat absorption, heat insulation and low radiation performance, but also the excellent high-temperature flexibility enables the series structure to be effectively attached to any surface and implement efficient infrared camouflage for up to 10 hours, ultimately ensuring that the obtained integrated ordered structure material exhibits excellent compatibility stealth protection capabilities against both static and dynamic heat sources, is more versatile and universal, breaks the dependence of traditional hydrogel-based infrared stealth materials on narrow application temperature zones, and has broad application prospects in the field of infrared thermal stealth; 3) By wrapping the high thermal resistance middle layer with all or part of the surface of the high enthalpy bottom layer except the bottom surface, and directly loading the low infrared emissivity top layer on the high thermal resistance middle layer by spraying and curing, the adhesion between the high enthalpy bottom layer and the low infrared emissivity top layer is enhanced to avoid desorption of the double layers due to stress friction (the polar groups in the low infrared emissivity top layer can form a strong chemical bond with the high thermal resistance middle layer made of polydimethylsiloxane resin, so that the low infrared emissivity top layer exhibits excellent level 1 bonding strength); 4) The integrated ordered structure material disclosed in the present invention can be adapted to different thermal targets of different states and temperatures when applied as a single layer (only the low infrared emissivity top layer), a double layer combination (a high enthalpy bottom layer and a low infrared emissivity top layer), and a three layer combination (a high enthalpy bottom layer, a high thermal resistance middle layer, and a low infrared emissivity top layer) (for low temperature thermal targets such as human bodies, only a single layer of the low infrared emissivity top layer can exhibit excellent thermal camouflage capabilities; for static medium temperature heat sources such as 80°C, the composite structure composed of the high enthalpy bottom layer and the low infrared emissivity top layer can achieve effective stealth protection for the medium temperature heat source from the perspectives of thermal conduction and thermal radiation; for dynamic medium temperature heat sources such as those with temperatures fluctuating in the range of 45 to 80°C, the composite structure composed of the high enthalpy bottom layer and the low infrared emissivity top layer can achieve effective stealth protection for the medium temperature heat source from the perspectives of thermal conduction and thermal radiation; for dynamic medium temperature heat sources such as those with temperatures fluctuating in the range of 45 to 80°C, the composite structure composed of the high enthalpy bottom layer and the low infrared emissivity top layer can achieve effective stealth protection for the medium temperature heat source from the perspectives of thermal conduction and thermal radiation. The structure can successfully suppress temperature fluctuations by utilizing the temperature hysteresis generated by phase change behavior; for static high-temperature heat sources such as 100°C, the composite structure composed of a high-enthalpy bottom layer, a high-thermal-resistance middle layer and a low-infrared-emissivity top layer can utilize polydimethylsiloxane resin with low thermal conductivity and adjustable thickness to effectively weaken the axial heat transfer in the structure, thereby solving the "weakness" of camouflage of single / two-combination components during high-temperature stealth; for dynamic high-temperature heat sources such as those with temperatures fluctuating in the range of 45 to 100°C, the composite structure composed of a high-enthalpy bottom layer, a high-thermal-resistance middle layer and a low-infrared-emissivity top layer can utilize its high phase change enthalpy to effectively weaken the temperature increase through melting behavior during the heating process and solidification behavior during the cooling process, thereby greatly reducing the exposure risk of dynamic thermal targets with high-frequency temperature changes).

[0024] The features and advantages of the present invention will be described in detail through embodiments in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a flow chart of the preparation of the high enthalpy bottom layer of Example 1; Figure 2 is a flow chart for preparing the low infrared emissivity top layer of Example 1; Figure 3 is a schematic structural diagram of an integrated ordered structure material of Example 1; Figure 4 This is a diagram of the infrared stealth mechanism of the integrated ordered structure material of Example 1; Figure 5 is a SEM image of the low infrared emissivity top layer prepared in Example 1 and Example 2; Figure 6 are infrared emissivity, mirror glossiness and adhesion strength graphs of the low infrared emissivity top layer prepared in Example 1 and Example 2; Figure 7 FTIR spectra of PVA hydrogel, SA, PVA and fatty acid-based phase change gel layers prepared in Example 1; Figure 8 The mechanical properties and physical pictures of the fatty acid-based phase change gel layers prepared in Example 1 and Example 3 at room temperature and 80°C; Fig. 9 is a SEM image of the fatty acid-based phase change gel layer prepared in Example 1 and Example 3; Fig.10 1 is a DSC curve diagram of pure stearic acid and fatty acid-based phase change gel layers prepared in Example 1 and Example 3; Fig.11 is a time-temperature curve of the integrated ordered structure material prepared in Example 1 and Example 4 on a heating table at 100° C.; Fig.12 This is an infrared thermal imaging image of the low infrared emissivity top layer prepared in Example 1 on the human body surface; Fig.13 It is an infrared thermal imaging image of the fatty acid-based phase change gel / infrared coating composite structure prepared in Example 1 on a static 80° C. heating table; Fig.14 It is an infrared thermal imaging image of the fatty acid-based phase change gel / infrared coating composite structure prepared in Example 1 on a dynamic heat source (45-80° C.); Fig.15 This is a stealth mechanism diagram of the composite structure composed of BPCG-75 and FC / Al-5 / 5 in Test Example 7; Fig.16 This is an infrared thermal image of the integrated ordered structure material prepared in Example 1 on a static 100° C. heating stage; Fig.17This is an infrared thermal imaging image of the integrated ordered structure material prepared in Example 1 on a dynamic heat source (45-100°C). DETAILED DESCRIPTION

[0026] Embodiment 1: The integrated ordered structure material was prepared according to the following steps: a) Preparation of high enthalpy bottom layer: See also Figure 1 First, 0.5 g of polyvinyl alcohol powder (PVA powder) was weighed and dissolved in 9.5 ml of deionized water under heating and stirring conditions at 80 ° C (stirring for 1.5 hours to promote the full dissolution and dispersion of polyvinyl alcohol); after the temperature of the polyvinyl alcohol solution (PVA solution) was lowered to room temperature, 1.5 g of stearic acid and 800 ul of hydrochloric acid were added to the polyvinyl alcohol solution in sequence and stirred for 1 hour to allow the polyvinyl alcohol to undergo a full esterification reaction with stearic acid under acidic conditions; then, 100 ul of glutaraldehyde solution was added to the polyvinyl alcohol / stearic acid mixed solution (PVA / SA solution), and the polyvinyl alcohol / stearic acid / glutaraldehyde hydrogel (PVA / SA / GA hydrogel) could be quickly formed within 5 minutes; then, the hydrogel was fully washed with deionized water until the pH value of the washing solution was 7, and then it was placed in an oven at 55 ° C for 20 hours to promote the complete volatilization of its water, thereby obtaining the final fatty acid-based phase change gel (PVA / SA / GA phase change gel), marked as BPCG-75; 75 represents the mass fraction of stearic acid in the composite phase change material; b) Preparation of high thermal resistance middle layer: A certain mass of dimethylsiloxane monomer and cross-linking agent were weighed in a mass ratio of 10:1 and poured into a mold containing BPCG-75 after being stirred evenly; next, after standing at room temperature for 30 minutes to eliminate bubbles, the assembled component was transferred to a vacuum drying oven at 55°C and cured at high temperature for 6 hours to obtain a high thermal resistance middle layer, which was marked as P4; wherein 4 represents the thickness of the polydimethylsiloxane resin layer and the unit is mm; c) Preparation of low infrared emissivity top layer: See also Figure 2, weigh 0.03g of fluorocarbon resin-A and 0.2g of fluorocarbon resin-B in a glass container, stir and mix thoroughly to obtain the resin matrix of the coating; then weigh 0.115g of flaky Al powder (Al powder) and disperse it in the resin matrix, and then add an appropriate amount of butyl acetate to adjust the viscosity of the coating to a suitable range (until it has good fluidity and no obvious particles formed by filler agglomeration are observed in the solution; the portion of the liquid other than Al powder is FEVE / Butylacetate solution; then, using a lithium electric pump spray pen, at 15PSI, the obtained coating was evenly sprayed onto the P4 surface (the coating thickness was limited to 250um by controlling the spraying distance and time); after drying at room temperature for 12 hours until the solvent butyl acetate was completely volatilized, the coating was placed in an oven at 55°C for curing for 5 hours, and finally a low-emissivity infrared coating (FC / AlCoating) was obtained and recorded as FC / Al-5 / 5; wherein 5 / 5 represents the mass ratio of fluorocarbon resin (0.23×50%, and 50% is the solid content (solid content refers to the ratio of the final mass to the initial mass after heating at 100°C in vacuum for 30 minutes)) to Al powder.

[0027] Finally, the structure and infrared stealth mechanism of the obtained integrated ordered structure material based on biomass phase change gel are as follows Figure 3 and Figure 4 As shown in the figure (FC / Al represents the top layer with low infrared emissivity, PDMS represents the middle layer with high thermal resistance, and BPCG represents the bottom layer with high enthalpy, the same below); the integrated ordered structure material has the following advantages: 1) On the one hand, stearic acid as the main phase change material is widely present in nature (can be directly extracted from animal fat and vegetable oil) and is environmentally friendly. On the other hand, fluorocarbon resin as the top heat radiation component is infrared transparent and chemically stable, and can effectively encapsulate cheap and readily available flake aluminum powder, thereby forming an extremely low far-infrared emissivity; 2) The preparation method is low-cost and simple, mainly through cross-linking and thermal curing connection; 3) The structure is simple and is a stable cylindrical whole composed of three parts (it should be emphasized that the shape of the integrated ordered structure material is determined by the shape of the mold, and the mold can be cylindrical, prism-shaped, truncated cone-shaped or other special shapes. Those skilled in the art should make adaptive modifications to the shape of the stealth system under the guidance of the embodiments of this specification, and no examples will be given in the embodiments); 4) It has thermal flexibility and can show excellent compatibility and stealth protection capabilities for static and dynamic uneven heat source surfaces.

[0028] Embodiment 2: The loading amount of Al powder was changed from 50wt% to 30wt%, 40wt%, 60wt% and 70wt%; the rest was the same as in Example 1.

[0029] Embodiment three: The loading amount of stearic acid was changed from 75wt% to 60wt%, 65wt%, 70wt% and 80wt%; the rest was the same as in Example 1.

[0030] Embodiment 4: The thickness of the polydimethylsiloxane resin layer was changed from 4.0 mm to 3.0 mm, 3.5 mm, 4.5 mm and 5.0 mm; the rest was the same as in Example 1.

[0031] Test example 1: For Example 1 and Example 2, the morphological features and optical properties of the infrared coating (i.e., the top layer with low infrared emissivity) are listed in Figure 5 and Figure 6 wherein FC / Al-5 / 5 is the pattern of Example 1 in which the loading amount of Al powder is controlled to 50wt%, and FC / Al-7 / 3, FC / Al-6 / 4, FC / Al-4 / 6 and FC / Al-3 / 7 are the patterns of Example 2 in which the loading amount of Al powder is controlled to 30wt%, 40wt%, 60wt% and 70wt%, respectively, the same below; in addition, Figure 6 In the figure, the incident angle of the mirror gloss is 60°.

[0032] like Figure 5 As shown in Figure 2, when the aluminum powder content is low (such as FC / Al-7 / 3), the functional filler cannot completely cover the entire surface of the coating; the strong infrared light absorption caused by a large number of pores and the deformed orientation of the aluminum powder caused by stress contraction will increase the emissivity of the coating (see Figure 6 (a)); when the aluminum content is too high (such as FC / Al-4 / 6 and FC / Al-3 / 7), the structure reflects visible light strongly due to the brightness of the metal, thus increasing the risk of visual exposure of the coating (see Figure 6 (b) of the FC / Al-5 / 5 coating. For FC / Al-5 / 5, the compact surface formed by the appropriate filler concentration ensures the orderly parallel arrangement of the flaky aluminum powder. The emissivity can be optimized from 0.255 to 0.221 when the aluminum powder dosage is 30wt%, which makes the coating have excellent ultra-low infrared emissivity and enhances its ability to reflect far-infrared radiation in the wavelength range of 8-14μm. In addition, good mechanical properties are also a basic requirement for the expansion of infrared coating applications. Figure 6In part (c), since the polar groups in the fluorocarbon resin can form a strong chemical bond with the substrate, when the aluminum powder content is lower than 50wt%, the FC / Al-x coating exhibits excellent level 1 bonding strength and can firmly adhere to the surface of the substrate, achieving effective thermal camouflage protection for thermal targets.

[0033] After comprehensively considering the infrared emissivity, glossiness and mechanical properties of the infrared coating, it was finally determined that the optimal total filler content in the coating was 50wt% and the average film thickness was 258um (see Figure 5 (f) of the Regulations).

[0034] Test Example 2: In order to improve the versatility of camouflage technology, the present invention further incorporates thermal management technology on the basis of stealth coating, thereby expanding the temperature range of "thermal stealth"; wherein, the composite phase change gel (i.e., fatty acid-based phase change gel layer) is prepared by two-step cross-linking of polyvinyl alcohol and stearic acid; Figure 1 As shown, in order to improve the encapsulation rate of the phase change material, in the first cross-linking step, the present invention utilizes the esterification reaction between polyvinyl alcohol and stearic acid under acidic conditions to cause part of the stearic acid to be linked to the long chain of polyvinyl alcohol to form chained stearic acid; in order to further encapsulate the remaining free stearic acid and improve the high-temperature anti-leakage properties of BPCG, glutaraldehyde is introduced into the polyvinyl alcohol / stearic acid mixed solution, and rapidly undergoes a condensation reaction with polyvinyl alcohol under acidic conditions (the large number of acetal bonds generated ensure the formation of a secondary cross-linking network, further strengthen the internal structure of BPCG, and enhance its reliability in practical applications); then, after simple solvent replacement and drying treatment, BPCG with high enthalpy characteristics is synthesized.

[0035] For Example 1, this test example uses FTIR spectroscopy to characterize the molecular structure and chemical bonds of the fatty acid-based phase change gel layer, and the results are as follows: Figure 7 shown.

[0036] Overall, BPCG-75 retains all characteristic peaks of polyvinyl alcohol and stearic acid. Specifically, compared with polyvinyl alcohol, BPCG-75 has a −1 The stretching vibration peak of OH at 1025 cm −1 The COC stretching vibration absorption peak at , which indicates that the carboxylic acid in the stearic acid component reacts with the hydroxyl group in the polyvinyl alcohol to form an esterification reaction; in addition, Figure 7 In the figure, PVA represents polyvinyl alcohol and SA represents stearic acid. To further illustrate the heavy cross-linking effect of glutaraldehyde, a polyvinyl alcohol hydrogel without stearic acid (i.e., PVA hydrogel) was also prepared in this experiment. −1The significant decrease in the peak at 1118 cm −1 The peak at 3437 cm −1 The slight red shift of the peak at supports the hypothesis that the cross-linking of the alcohol group of polyvinyl alcohol and the CHO group of glutaraldehyde leads to the formation of ether (CO-) and acetal ring (COC); thus, the use of FTIR provides strong evidence for the two-step cross-linking of the fatty acid-based phase change gel layer.

[0037] Test Example 3: For Example 1 and Example 3, this test example used a universal material testing machine to perform tensile tests on each sample, and the results are as follows: Figure 8 As shown; among them, Figure 8 Part (a) shows the elastic modulus, tensile strength and elongation at break of each sample of Example 1 and Example 3 at room temperature, while Figure 8 Part (b) shows the stress-strain curve of BPCG-75 at 80°C; BPCG-60, BPCG-65, BPCG-70 and BPCG-80 represent stearic acid loadings of 60wt%, 65wt%, 70wt% and 80wt%, respectively, the same below.

[0038] See also Figure 8 As shown in Table 1, due to the evaporation of the solvent water in the phase change gel, the polyvinyl alcohol layer directly encapsulates stearic acid through a two-step cross-linking reaction. The polyvinyl alcohol as the continuous phase is interrupted by the discretely distributed stearic acid, and stress concentration points appear during the stretching process. Therefore, all samples show brittle fracture characteristics at room temperature, and the elongation at break is generally below 6%; Interestingly, with the increase of stearic acid content, the elastic modulus and tensile strength of the fatty acid-based phase change gel layer decrease as a whole, and the elongation at break shows a "volcano" type change, and reaches a peak at BPCG-75; The reason for this phenomenon may be related to Compared with stearic acid, the hardness of dry polyvinyl alcohol gel is higher; in addition, compared with other styles, the three-dimensional continuous fibrous grid of BPCG-75 is denser (the compact network structure is conducive to dispersing the concentrated stress during the stretching process, thereby causing a decrease in tensile strength and an increase in elongation at break); when the temperature is further increased to above the melting point of stearic acid, the stearic acid in a liquid flow state makes the tensile stress widely distributed, effectively reducing the tendency of brittle fracture, and showing amazing flexibility and stretchability; for Example 1, its elastic modulus, tensile strength and elongation at break are 3.70 MPa, 0.59 MPa and 85.78% respectively, and it can be easily bent under the pressure of an adult's palm (such as Figure 8 (as shown in part (c) of the diagram).

[0039] Therefore, from the perspective of mechanical properties, BPCG-75 not only exhibits relatively better adaptability at room temperature, but also has excellent flexibility in high temperature environments, making it easier to meet the needs of complex application environments; in addition, Fig. 9 The surface morphology characteristics of BPCG-60, BPCG-65, BPCG-70, BPCG-75 and BPCG-80 are displayed; when the relative content of stearic acid increases from 60wt% to 75wt%, as the degree of two-step crosslinking gradually deepens, the SEM images show progressively densely packed worm-like rod structures; however, when the stearic acid content is too high, such as BPCG-80 (stearic acid loading is 80wt%), too much stearic acid will be wrapped on the surface of the rod structure, forming a "rock"-like appearance of stacked and interlaced blocks; therefore, a moderate amount of phase change material encapsulation is crucial for the formation of three-dimensional continuous fibrous grids in the composite structure (75wt% stearic acid addition is preferred).

[0040] Table 1 Mechanical properties of various patterns of Example 1 and Example 3

[0041]

[0042] Test Example 4: For Example 1 and Example 3, this test example used a differential scanning calorimeter to test the heat flow curves of the phase change process of each sample. The results are listed in Fig.10 Among them, Fig.10 Part (a) is the DSC curve of stearic acid. Fig.10 Part (b) shows the results of the above-mentioned samples in the heating stage, while part (c) shows the results of the above-mentioned samples in the cooling stage.

[0043] Compared with stearic acid, which undergoes a spontaneous phase transition (see Fig.10 As shown in part (a) of the above-mentioned samples, the phase change peaks of the above-mentioned samples show staged endothermic and exothermic behavior; this two-stage phase change behavior may be caused by the different properties of the chained stearic acid and the free stearic acid in the above-mentioned samples; among them, compared with the chained stearic acid, the chemical environment of the free stearic acid is freer and is not constrained by the associated ester bond, so it is the first to thermally yield in the temperature rise stage; with the further increase in temperature, the stronger phase change thermal driving force increases the lattice change of the chained stearic acid and the movement tendency of the molecular chain, thereby prompting the above-mentioned samples to show a bimodal endothermic behavior; similarly, in the cooling stage, the successive phase changes of the free stearic acid and the chained stearic acid contribute to the first and second exothermic peaks on the DSC curve respectively.

[0044] In general, since the amount of added polymer base polyvinyl alcohol and cross-linking agent is always much lower than that of the main phase change material stearic acid, the phase change parameters of the above-mentioned patterns do not change much compared with pure stearic acid (see Table 2).

[0045] Table 2 DSC curve data of each sample of Example 1 and Example 3

[0046]

[0047] In Table 2, the unit of temperature is °C and the unit of enthalpy is J / g.

[0048] Test Example 5: For Example 1 and Example 4, this test example uses a data collector to record the surface temperature of the stealth system, and the results are listed in Fig.11 middle.

[0049] like Fig.11 As shown in the figure, the contribution of the polydimethylsiloxane resin layer to thermal insulation with a gradient thickening of 0.5 mm is weakened successively, and the surface middle section temperature of the series structure is balanced at 70°C, 63°C, 59°C, 56°C and 54°C respectively; therefore, the degree of temperature weakening for each 0.5 mm thickening of the polydimethylsiloxane resin layer is nonlinear; although blindly thickening the polydimethylsiloxane resin layer can effectively reduce the average surface temperature of the stealth system, this is at the expense of the overall height of the series structure (reducing its application potential in a small space).

[0050] Test Example 6: Taking Example 1 as an example, for low-temperature thermal targets such as human bodies (humans are warm-blooded animals with high infrared ε, and their apparent temperature is approximately 36°C), a single-layer low infrared emissivity top layer can already demonstrate excellent thermal camouflage capabilities; specifically, after FC / Al-5 / 5 is sprayed on the surface of nitrile gloves by a high-pressure air gun (15PSI) and worn for 60 minutes, its average radiation temperature is stabilized at 25.1°C (see Fig.12 ); Compared with the temperature of the exposed part (38.1℃), FC / Al-5 / 5 effectively reduces the temperature difference between the human body and the environment, significantly changes the thermal infrared radiation characteristics of the human body, and can achieve reliable infrared detection protection for human heat sources.

[0051] Test Example 7: Taking Example 1 as an example, for a static medium-temperature heat source of 80°C, the composite structure composed of BPCG-75 and FC / Al-5 / 5 can achieve effective stealth protection for the medium-temperature heat source from the perspectives of heat conduction and heat radiation; specifically, after 120 minutes, the average surface temperature of the composite structure is stabilized at around 63.9°C; after the infrared coating further attenuates the heat radiation, its average radiation temperature is only 41.4°C (see Fig.13In addition, for dynamic medium-temperature heat sources with temperature fluctuations in the range of 45 to 80°C, the composite structure successfully suppressed temperature fluctuations by utilizing the temperature hysteresis generated by phase change behavior (the temperature fluctuation range can be reduced from 37.4°C to 19.6°C), and the fluctuation of radiation temperature was stabilized within 9.2°C (see Fig.14 ).

[0052] The stealth mechanism of the composite structure is as follows Fig.15 As shown; among them, BPCG-75, as a super absorber of heat, can use the phase change enthalpy (high thermal enthalpy of 152.6 kJ / kg) to fully absorb the heat of the heat conduction process, optimize the radiation bright spot of the single infrared coating in a medium temperature environment, and increase the axial heat transfer resistance; at the same time, the layers of flaky Al powder in FC / Al-5 / 5 can reflect thermal radiation at multiple levels to achieve "thermal camouflage" of the apparent temperature.

[0053] Test Example 8: Taking Example 1 as an example, for a static high-temperature heat source of 100°C, the stealth system composed of BPCG-75, P4 and FC / Al-5 / 5 can use polydimethylsiloxane resin with a thermal conductivity of only 0.15 W / m·K to effectively weaken the axial heat transfer in the structure and solve the camouflage "weakness" of single / two-combination components during high-temperature stealth. The average radiation temperature after 10 hours is only 39.4°C (see Fig.16 ); For dynamic high-temperature heat sources with temperature fluctuations in the range of 45 to 100°C, the stealth system uses its high phase change enthalpy to effectively weaken the temperature increase through melting behavior during the heating process and solidification behavior during the cooling process; after the polydimethylsiloxane resin effectively slows down the response of the internal temperature to external changes and the reliable thermal radiation attenuation of the infrared coating, the fluctuation of the radiation temperature is finally limited to the range of 8.6°C (see Fig.17 ), the temperature fluctuation suppression rate is as high as 84.4%, which greatly reduces the exposure risk of dynamic thermal targets with high-frequency temperature changes.

[0054] The above embodiments are intended to illustrate the present invention, not to limit the present invention. Any solution that is a simple transformation of the present invention belongs to the protection scope of the present invention.

Claims

1. An integrated ordered structure material, characterized in that: It comprises a high enthalpy bottom layer and a low infrared emissivity top layer arranged in sequence, wherein the high enthalpy bottom layer is a thermally stable gel layer solidified by a high-capacity phase change material, and the low infrared emissivity top layer is an infrared transparent resin layer filled with metal fillers.

2. The integrated ordered structure material according to claim 1, characterized in that: A high thermal resistance middle layer is also provided between the high enthalpy bottom layer and the low infrared emissivity top layer, and the high thermal resistance middle layer is a polydimethylsiloxane resin layer.

3. The integrated ordered structure material according to claim 2, characterized in that: The high thermal resistance middle layer is coated on all or part of the surface of the high enthalpy bottom layer except the bottom surface, and the low infrared emissivity top layer is coated on the top surface of the high thermal resistance middle layer.

4. The integrated ordered structure material according to claim 3, characterized in that: The thickness of the high thermal resistance middle layer is controlled within the range of 3.0 to 5.0 mm, and the thickness of the low infrared emissivity top layer is controlled within the range of 220 to 280 um.

5. The integrated ordered structure material according to claim 4, characterized in that: The high enthalpy bottom layer exhibits a progressively densely packed worm-like rod structure, and the low infrared emissivity top layer is in the form of metal fillers stacked layer by layer in an infrared transparent resin layer.

6. The method for preparing an integrated ordered structure material according to any one of claims 2 to 5, characterized in that: The steps include: a) Preparation of the high enthalpy bottom layer: firstly, polyvinyl alcohol, fatty acid, acid reagent and aldehyde cross-linking agent are sequentially mixed and reacted, then the mixed solution is solidified and formed, and then washed and dried in sequence to obtain a fatty acid-based phase change gel layer as the high enthalpy bottom layer; b) Preparation of high thermal resistance middle layer: firstly, dimethylsiloxane monomer and cross-linking agent are uniformly mixed and poured into a mold with high enthalpy bottom layer, and then the mixed liquid is cured outside the high enthalpy bottom layer to form a high thermal resistance middle layer; c) Preparation of the low infrared emissivity top layer: First, the metal filler is evenly dispersed in the infrared transparent resin substrate, and then the dispersion is sprayed on the outside of the high thermal resistance middle layer and cured to form a low infrared emissivity top layer.

7. The method for preparing an integrated ordered structure material according to claim 6, characterized in that: In the step a), the loading amount of the fatty acid is 60 to 80 wt %, the mass volume ratio of the fatty acid to the acidic reagent is 0.001 to 0.003 g / ul, the volume ratio of the acidic reagent to the aldehyde cross-linking agent is 6 to 10:1, the fatty acid is one or a combination of capric acid, lauric acid, myristic acid, palmitic acid and stearic acid, the acidic reagent is hydrochloric acid, and the aldehyde cross-linking agent is one or a combination of formaldehyde, acetaldehyde, n-butyraldehyde, glutaraldehyde and crotonaldehyde.

8. The method for preparing an integrated ordered structure material according to claim 6, characterized in that: In the step b), the mass ratio of the dimethylsiloxane monomer to the cross-linking agent is 8 to 12:

1.

9. The method for preparing an integrated ordered structure material according to claim 6, characterized in that: In the step c), the loading amount of the metal filler is 30 to 70 wt %, the metal filler is one or a combination of aluminum powder, iron powder, zinc powder, silver powder and gold powder, the shape of the metal filler is one or a combination of spherical, rod-shaped, scaly and irregular shapes, the maximum distance between two points of the metal filler on the surface is controlled to be 20 to 25 um, and the infrared transparent resin is one or a combination of fluorocarbon resin, epoxy resin, polyurethane resin and acrylic resin.

10. Application of the integrated ordered structure material according to any one of claims 1 to 5 in infrared stealth.

Citation Information

Patent Citations

  • Preparation method of composite coating layer for controlling infrared radiation

    CN106867385A

  • Preparation method of shape-stable phase-change material

    CN111793473A

  • Infrared stealth composite material with sandwich structure

    CN112937029A

  • Heat radiation inhibition laminated structure, preparation method and application thereof

    CN115257096A

  • Infrared / electromagnetic double-stealth polypyrrole-coated polyimide hybrid aerogel / phase change material composite membrane and preparation method thereof

    CN115449121A